Postmodernism Aspects in Lens of Baudrillard Theory in the novels DeLillo’s white noise and Atwood `s Handmaid’s tale - Fatemeh Sadat Basirizadeh; Narges Raoufzadeh; Shahrzad Mohammadhossein; Muhammad Natsir; Fauziah Khairani Lubis (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
This paper focuses on Postmodernism Aspects in Lens of Baudrillard Theory in the novels DeLillo’s white noise and Atwood `s Handmaid’s tale. To consider the United States as our case study, we know that the affluence and waste are quite related to each other. In a way that we might count it as a throwaway society or garbage can sociology like how Baudrillard has put in words. We are cognizant of the fact that all moralists have criticized the lavishing of wealth. An individual who does not comply with the moral law regarding the internal use-value of commodities. The mystification of the commonplace in White Noise can be interpreted as a revolt towards Modernism, which equated rationalization with an increased and general knowledge of the condition under which one lives, i.e., the belief that there are no mysterious incalculable forces that come into play. Modernism located the romantic idea of mystery, of the unknown, geographically, in faraway places like Africa or America. The Handmaid's Tale suggests a particularly postmodern feminist space for resistance a space located within the discourses of the symbolic order including technologically produced and disseminated discourses) rather than in opposition to them.